Pengaruh Promosi Penjualan Dan Iklan Terhadap Minat Beli Grabfood Kota Bogor (Studi Pada Konsumen GrabFood Kota Bogor) - Fatharani, Aurelia Putri; Hidayat, Agus Maolana (eProceedings of Management, 2023)
In the world of online food delivery, which is booming in this era of globalization, competition between applicationbrands is getting tougher, one of which is GrabFood. This is due to the development of technology that makespeople use food delivery applications more often. Usually people choose food delivery applications based onpromos and advertisements offered by the company, so in this case it has an impact on consumer buying interest.The purpose of this study was to determine the effect of sales promotion and advertising on the purchase intentionof GrabFood in Bogor partially and simultaneously. This study uses quantitative methods with descriptive andcausal analysis. Sampling using non-probability sampling technique and purposive sampling method involving100 respondents. The results of the data in this study were processed using the Software Statistical Program of SocialScience (SPSS) version 24.The results of the descriptive analysis show that the variables of sales promotion,advertising and buying interest as a whole are included in the very good category. Based on the hypothesis test,the results of this study are that there is a positive and significant effect of sales promotion and advertising on thepurchase intention of GrabFood in Bogor partially and simultaneously.Keywords-sales promotion, advertising, buying interest